2021
DOI: 10.3390/molecules26196018
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Derived Tumor Chemosensitization of GKB202, an Antrodia Cinnamomea Mycelium-Derived Bioactive Compound

Abstract: Oral cancers, hepatocellular carcinoma, and colorectal cancers are the three most common cancers, leading to 18,000 cases of cancer-related mortality in Taiwan per year. To bridge the gap towards clinical translation, we developed a circulating tumor cell (CTC) organoid culture workflow that efficiently expands CTC from patients to test Antrodia Cinnamomea mycelium-derived bioactive compounds. Three ACM-derived bioactive compounds were evaluated for tumor chemosensitization characteristics. Significant and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…This result is reasonable, judging from t 1/2 values, because rat liver has been reported to metabolize faster than human liver [28]. Compared with other compound reports using rat liver S9, GKB202 of the Antrodia cinnamomea mycelium (t 1/2 = 3.68 min) was metabolized more rapidly than erinacine A [29]. The previous report showed that there was no-observed-adverse-effect of 3 g/kg body weight/day erinacine A-enriched HE in 28-day oral feeding in Sprague-Dawley rats.…”
Section: Quantification Of Erinacine a In Rat And Human Liver S9 Anal...supporting
confidence: 63%
“…This result is reasonable, judging from t 1/2 values, because rat liver has been reported to metabolize faster than human liver [28]. Compared with other compound reports using rat liver S9, GKB202 of the Antrodia cinnamomea mycelium (t 1/2 = 3.68 min) was metabolized more rapidly than erinacine A [29]. The previous report showed that there was no-observed-adverse-effect of 3 g/kg body weight/day erinacine A-enriched HE in 28-day oral feeding in Sprague-Dawley rats.…”
Section: Quantification Of Erinacine a In Rat And Human Liver S9 Anal...supporting
confidence: 63%
“…The clinical application of circulating tumor cells has many purposes, including as therapeutic targets for metastatic tumors, early diagnosis, prognosis prediction, and real-time molecular phenotyping and minimal invasive liquid biopsies [ 31 ]. Furthermore, CTCs serve as a drug testing platform provided by living cells [ 32 ], and a correlation between CTC drug sensitivity profiles and the treatment response has been demonstrated in patients with pancreatic duct adenocarcinoma [ 17 ]. Recently, the application of CTCs to brain tumor treatment has been associated with great concern and has been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Combination treatment with talazoparib (a PARP inhibitor) and CX-5461 (an inhibitor of RNA polymerase I transcription and an activator of the DNA damage response) might be a promising candidate treatment for HR-proficient patients who are not suitable for PARP inhibitor monotherapy, which was verified by increased DNA damage and decreased growth of organoids derived from HR-proficient castrate-resistant PC after treatment [177]. Based on tumoroids generated from circulating tumor cells of patients with HCC, oral cancer, or CRC, the Antrodia cinnamomea mycelium-derived bioactive compound GKB202 was indicated to be a promising adjuvant and enhancer for 5-FU-based treatment [178]. Collectively, organoids might serve as an excellent platform to explore novel and promising combination treatment strategies for patients with intractable tumor types.…”
Section: Exploration Of Promising Combination Treatment Strategiesmentioning
confidence: 99%